Actividad antibacteriana de extractos de hongos aislados de raíces del mangle Rhizophora mangle (Rhizophoraceae) en Venezuela - Castillo Machalskis, Isabel (2007)
The antibacterial activity of marine fungi extracts was evaluated by a test of efficiency. The fungi were previously inoculated in Malt Agar (EMA) extract with 50 % of seawater and growth for 60 days. Triplicate antibiograms were carried out with the extracts. An ANOVA I with a posteriori Duncan test were applied to the diameters of inhibition zones. The extracts of Aspergillus ochraceus 3MCMC3 and Penicillium citrinum (14) 4MCMC16 present wide spectral antibacterial properties, inhibiting 100 % and 80 % of the developing germs, especially Pseudomonas aeruginosa 9027. The extract of Penicillium (1) 3MLLC5 had the highest efficiency on this strain; P. aeruginosa 9027 and Escherichia coli 10536 were the most sensitive germs when treated with these extracts. These marine fungi can be an important source of antibacterial secondary metabolites.